2016
DOI: 10.1002/lary.26135
|View full text |Cite
|
Sign up to set email alerts
|

Low surgical complication rates in cochlear implantation for young children less than 1 year of age

Abstract: 4. Laryngoscope, 127:720-724, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…10,11 It is this principle—substantiated by superior performance outcomes and the growing evidence for safety in implanting in infancy—that is supporting the growing practice of pediatric implantation within the first 2 years of life. 12,13…”
mentioning
confidence: 99%
“…10,11 It is this principle—substantiated by superior performance outcomes and the growing evidence for safety in implanting in infancy—that is supporting the growing practice of pediatric implantation within the first 2 years of life. 12,13…”
mentioning
confidence: 99%
“…Due to thinner skin flaps in very young infants, there have been concerns about increased risks of soft tissue complications including skin breakdown 37 . However, Kalejaiye et al reported a soft tissue complication rate of 1.33%, which is comparable to other reported rates in the literature 35,39‐41 …”
Section: Safety and Feasibilitymentioning
confidence: 90%
“…The incidence of a 30‐day post‐operative surgical complication using the American College of Surgeons National Surgical Quality Improvement Program (ACS‐NSQIP) pediatric database was 3.6% for infants <12 months compared with 3.2% for infants 12‐18 months ( P = 1.0) 38 . In a similar large retrospective review of 1278 patients from the ACS‐NSQIP database, Kalejaiye et al showed no significant differences in complication rates (2.73% vs 1.48%, P = .96) when comparing CI recipients <12 months (n = 73) to those >12 months 39 . Patients <12 months were noted to have longer mean operative times (191 minutes vs 160 minutes, P = .0015), which may be attributed to smaller skull size and less developed mastoid cavity with more bone marrow.…”
Section: Safety and Feasibilitymentioning
confidence: 95%
“…By examining the list of reasons why the child had not undergone CI, we see that 17% of parents were concerned about the risk of surgery. Given the low incidence of complication in CI surgery (29), proper education of parents by the surgeon may help increase the likelihood of implantation in potential candidates. For 83% of parents, the source of information for CI was from non-surgeon perspectives.…”
Section: Discussionmentioning
confidence: 99%